Samuel Barber : his life and legacy - Pollack, Howard (University of Illinois Press, 2023)
"A pivotal twentieth-century composer, Samuel Barber earned a long list of honors and accolades that included two Pulitzer Prizes for Music and the public support of figures like Serge Koussevitzky and Marian Anderson. Barber's works have since became standard in concert repertoire and continue to flourish across high art and popular culture. Acclaimed biographer Howard Pollack (George Gershwin, Aaron Copland) offers a multifaceted account of Barber's life and music while placing the artist in his social and cultural milieu. Born into a musical extended family, Barber pursued his ambitions from childhood. Pollack follows Barber's path from his precocious youth and training through a career where, from the start, the composer consistently received prizes, fellowships, and other recognition. Stylistic analyses of works like Adagio for Strings, the Second Symphony, the opera Vanessa, and Piano Concerto No. 1 stand alongside revealing accounts of the music's commissioning, performance, reception, and legacy. Throughout, Pollack weaves in accounts of Barber's encounters with musical contemporaries like Leonard Bernstein and Dmitri Mitropoulos, performers from Eleanor Steber and Leontyne Price to Vladimir Horowitz, patrons, admirers, and a wide circle of friends and acquaintances in and out of the arts. He also provides an eloquent portrait of the composer's decades-long relationship with, and break from, Gian Carlo Menotti. Informed by new interviews and immense archival research, Samuel Barber is the long-awaited critical and personal biography of a monumental figure in twentieth-century American music"-- Provided by publisher.
Keywords: Barber, Samuel, -- 1910-1981.; Barber, Samuel, -- 1910-1981; Composers -- United States -- Biography.; Compositeurs -- États-Unis -- Biographies.; MUSIC / General; Composers; United States; Biographies